Building Motivation for Learning Indonesian Language: Psychological and Social Strategies - Rulyandi, Rulyandi; Nasri, Ulyan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Acquiring proficiency in Indonesian involves diverse psychological and social elements shaping learners' motivation. This abstract examines strategies to enhance motivation for Indonesian language acquisition, drawing from psychological and social insights. Understanding these strategies is pivotal for educators and learners to optimize language learning outcomes. This study adopts a mixed-method approach, integrating quantitative and qualitative analyses. Data collection includes surveys identifying intrinsic and extrinsic motivational factors impacting Indonesian language learning, alongside in-depth interviews to delve into students' motivational experiences. Quantitative analysis involves descriptive and regression statistical techniques to reveal relationships between motivational factors and language proficiency. Qualitative analysis employs coding and thematic processes to uncover motivational patterns from interviews. Results highlight intrinsic factors like personal interest and satisfaction as key in sustaining motivation. Meanwhile, extrinsic factors such as recognition also influence motivation significantly. These findings stress the importance of a holistic approach to motivation in language learning. Implications underscore educators' need to address both intrinsic and extrinsic motivators in designing effective learning strategies. Utilizing a comprehensive psychological and social framework, educators can create supportive environments fostering higher Indonesian language proficiency. This can positively impact academic performance and personal growth.